Centennial Knowledge of Medicinal Plants Held in Communities of Espírito Santo, Brazil - Baliano, A. P.; Alves, F. S.; Pereira, A.C. H.; Aquije, G.M. de F.V.; Lenz, D.; Andrande, T. U.; Endringer, D. C. (Ethnobotany Research and Applications, 2015)
<!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> <![endif]–> <!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> The naturalist Auguste Saint-Hilaire, during a visit to Espírito Santo in 1826, recorded the popular use of some native plants, cited by the vernacular names fedegoso-do-mato, milhomens, erva-do-brejo, taririquim, batata-de-junça, and jarro. The aim of this study was to collect and systematize information about popular medicinal plants used in Afonso Cláudio, including the ones mentioned by Saint-Hilaire. The method used was a semi-structured snowball type research. Most of the 34 participants reported to know some of the plants cited by Saint-Hilaire, except the one known as jarro. The use of 156 ethnospecies was recorded, 60 of them were collected. These plants belong to 30 families, predominantly Lamiaceae and Asteraceae. Most of them were indicated to treat cough and stomach problems. The results indicate that in the area there is knowledge of native and exotic medicinal plants, and the species mentioned by Saint-Hilaire are still remembered. <!–[if gte mso 9]> Normal 0 false false false PT-BR X-NONE X-NONE <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin-top:0in; mso-para-margin-right:0in; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0in; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-ansi-language:PT-BR; –> <!–[endif] –>